The Patterns of Clinical Presentation, Treatment, and Survival Outcome of Wilm’s Tumor: A Six-Year Retrospective Study at a Single Cancer Institute - Alfaqaih, Sarah; Ghlio, Nowara; Abusanuga, Muna (Khalij-Libya Journal of Dental and Medical Research, 2024)
Background: Wilm’s tumor (WT) is recognized as the fourth most common pediatric cancer in the United States and accounts for more than 90% of all kidney malignancies identified among children. The 5-year overall survival exceeds 90% among developed countries. The objective of this study was to look at presentation and treatment patterns, as well as figure out the outcome of WT in Libya. Material and method: This was a retrospective cohort research conducted between July 2017 and October 2023. We have included information on basic demographic data, clinical presentation, laboratory values, radiologic evaluation, treatment protocol, and survival months. Results: There were 38 patients, female accounts for 20 (52.6%), and the median age at presentation was 38 months (IQR 18-56.25). The most frequent presentation was palpable abdominal mass, accounting for 78.9% (30 cases). The majority of cases were late presentations at either stage III or IV, 19 (50%) and 4 (10.5%), respectively. With a median follow-up duration of 15.5 months (ranging from 3 to 70 months), the overall 5-year survival rate is 94.7%. Survival rates for children who presented with stage II and stage III were 80% and 94.7%, respectively. Conclusions: In conclusion, in our setting, children with Wilm’s tumors present late with advanced disease and large tumors. A multidisciplinary approach can reasonably improve survival rates even in late presentations and in resource-limited scenarios. الخلفية: يُعترف بورم ويلم كثالث أكثر سرطان شائع للأطفال في الولايات المتحدة ويمثل أكثر من 90٪ من جميع الأورام الخبيثة في الكلى المحددة بين الأطفال. استنادًا إلى سجل السرطان التابع لمنظمة الصحة العالمية ، تحتل ليبيا أدنى معدل موحَّد حسب العمر (ASR) لأورام ويلم في إفريقيا. كان هدف هذه الدراسة هو دراسة أنماط العرض والعلاج ، بالإضافة إلى تحديد نتائج WT في ليبيا. المواد والطرق: كانت هذه دراسة انسجامية استقصائية أُجريت بين يوليو 2017 وأكتوبر 2023. قمنا بتضمين معلومات عن البيانات الديمغرافية الأساسية ، والعروض السريرية ، وقيم المختبرات ، والتقييم بالأشعة ، وبروتوكولات العلاج ، وشهور البقاء على قيد الحياة. كان هناك 38 مريضًا ، حسابات إناث تصل إلى 20 (52.6٪) ، وكان عُمر التقديم المتوسط ​​38 شهرًا (IQR 18-56.25). كان أكثر عروض التقديم شيوعًا كتلة بطنية قابلة للشعور، تصل نسبتها إلى 78.9٪ (30 حالة). كان مُعظَّلا مُغْصِّلا لغالبية حالات التقديم في مستوى III أو IV، 19 (50٪) و4 (10.5٪) على التوالى. مع فترة متابعة من 15.5 شهرًا (تترواح من 3 إلى 70 شهرًا)، نسبة بقاء خمس سنوات هى 94.7%. في الختام، يظهر الأطفال الذين يعانون من أورام ويلم بشكل متأخر مع المرض المتقدم والأورام الكبيرة. يمكن أن يحسن النهج التعددي الاختصاصات معدلات البقاء بشكل معقول حتى في الحالات المتأخرة وفي سيناريوهات ذات موارد محدودة